Pendekatan Etnokimia dalam Pendidikan Kimia: Literature Review Terhadap Berbagai Metode dan Penerapannya - Haris Munandar; Thayban Thayban; Erga Kurniawati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to review various methods and applications of the ethnochemistry approach in chemistry education through a literature review. Ethnochemistry connects chemical concepts with local wisdom and culture, providing deeper contextualization for students. The literature review was conducted by collecting data from various articles relevant to this topic, published between 2018 and 2024. The review results indicate that integrating ethnochemistry into chemistry learning can enhance students' understanding of chemical concepts, scientific skills, creativity, and engagement. This approach also helps preserve traditional chemical knowledge that may otherwise be lost. This study concludes that ethnochemistry is a significant innovation that can improve the quality of chemistry education in a more meaningful and relevant way for students, while also strengthening their cultural identity.